Penyelesaian Sengketa Atas Tumpang Tindih Kepemilikan Hak Atas Tanah Yang Mengalami Pembebasan Lahan Untuk Kepentingan Umum - Hosrizul Hosrizul; Joko Sriwidodo; Mohamad Ismed (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
Landowners affected by land acquisition initiatives in the public interest, especially for the government's benefit, frequently have trouble receiving compensation, as government and private sector property purchases are common. On the land, there was an overlapping ownership dispute, which delayed the land acquisition because it had to be resolved in court. This study's objective is to examine and appraise techniques for resolving overlapping land ownership disputes and the legal certainty of property rights for which land acquisition is to be done. The author uses normative and empirical legal methods in this study. Because normative legal research focuses on law or norms, the author uses a normative technique. Rules include legal principles, value rules, and legal restrictions. Legally normative study involves legal theory, the legal system, and vertical and horizontal synchronization. Due to overlapping land ownership generated by the buying and selling of land rights, the legal certainty of land rights for which land acquisition is to be done has not been adequately accomplished. The Camat who served as PPAT in the aforementioned case acquired the same block of land, which was not in the public's best interest.